Effects of employees’ physical and psychological characteristics over manufacturing systems’ performance (2018)
One of the main challenges in Macroergonomics is to develop a universal model to measure macroergonomic compatibility. As a first step to develop such model, it is necessary to validate the construct of macroergonomic compatibility (MC). MC refers to the ability of the different work system components and elements to complement the capabilities and limitations of employees in order to achieve companies’ goals. In that regard, to achieve this step, this paper analyzes the effects of MC of physical and psychological characteristics of employees over the performance of manufacturing systems measured by the clients, production processes, and the organizational performance of companies. Data was obtained from 188 employees of manufacturing systems by means of the Macroergonomic Compatibility Questionnaire (MCQ) in Chihuahua, Mexico. Also, data is analyzed to propose and test a hypothetical causal model of the relationships among the variables by using a Structural Equation Modeling (SEM) approach. Employees’ physical characteristics (weight, height, strength) are considered as independent variable. The highest direct effects values (ß) were found from physical characteristics to psychological characteristics (0,49), from clients to organizational performance (0,45), and from psychological characteristics to motivation and needs. Also, the highest total effects were found from physical characteristics to motivation and needs (0,517) and psychological characteristics (0,488) and from clients to organizational performance (0,454). Results of this model offer relevant knowledge to develop macroergonomic strategies for manufacturing systems in order to increase their competitiveness and support the design and improvement of these systems.